Auto generate men cloth template - Nurulfarhana, Mohd Azhar (2012)
Auto Generate template Men Cloth is acts as a platform for the user to make their cloth easy and faster. This prototype is a web-based system that is provides features of managing data and displaying the results of the template cloth. The objectives of the researh are to make an easy for user to auto generate the template by inserting the measurement of their body to the form in the interface. The methodology that used to develop this system is Rapid Application Development (RAD). The technique that will be use is canvas in HTML which is the input of the measurement is converting to the coordinate to make the pola. As the expected result is, the template is able to auto generate following the measurement that user insert whereby the measurement has key in by them.